Distribution, sources and transport of organophosphorus flame retardants in the water and sediment of Ny-Ålesund, Svalbard, the Arctic. (September 2020) - Gao, Xiaozhong; Xu, Yiping; Ma, Mei; Huang, Qinghui; Gabrielsen, Geir Wing; Hallanger, Ingeborg; Rao, Kaifeng; Lu, Zhibo; Wang, Zijian
Abstract: Organophosphorus flame retardants (PFRs) are contaminants of emerging concern which have been detected globally. However, little information on PFRs in the Arctic freshwater environment is currently available. In this study, both hydrophilic and hydrophobic PFRs in the water and sediment of four areas (town, surroundings, coastal marine water, and glacier melt runoff) near Ny-Ålesund Svalbard were investigated by time-integrated passive sampling (water) and grab sampling (sediment). Seven kinds of PFRs were found in the Arctic waters with individual freely dissolved concentrations from 0.007 ng L −1 to 355 ng L −1, and the concentrations of chlorinated PFRs were 3–4 orders of magnitude higher than those of non-chlorinated PFRs. The distribution of different PFRs in freshwater showed significant spatial differences among the different areas, and the town was found to have most kinds of PFRs and highest PFRs concentrations. The sources and transport of different kinds of PFRs were explored based on a spatial overlay analysis of the contaminant distributions, environmental conditions, and PFR applications. As a result, human settlements, industrial activities, atmospheric deposition, and transportation in Ny-Ålesund were proposed to be related to the pollution of different PFRs at Ny-Ålesund. The PFRs in the inshore marine water were found to be affected by both local ship contamination and ocean current transport. Furthermore, nine PFRs were detected in the sediments of Ny-Ålesund. Accumulation of different PFRs in the Arctic sediment was found to be dominated by their physico-chemical properties (polarity). Graphical abstract: Image 1 Highlights: Organophosphorus flame retardants (PFRs) were found in Arctic freshwater environment. Two kinds of passive sampler were coupled to monitor twelve PFRs in the water. Sources and transport of PFRs in the Arctic aquatic environment were explored. Chlorinated PFRs pollution at Ny-Ålesund may be related to atmospheric transport. Accumulation of PFRs in the sediment was dominated by their chemical polarities. Abstract : The distribution, sources, and transport of PFRs in the water and sediment of different areas near Ny-Ålesund, Svalbard, the Arctic, were studied.